1985
DOI: 10.1021/bi00341a048
|View full text |Cite
|
Sign up to set email alerts
|

Studies on inactivation of lipoprotein lipase: role of the dimer to monomer dissociation

Abstract: Sedimentation equilibrium analysis demonstrated that preparations of bovine lipoprotein lipase contain a complex mixture of dimers and higher oligomers of enzyme protein. Enzyme activity profiles from sedimentation equilibrium as well as from gel filtration indicated that activity is associated almost exclusively with the dimer fraction. To explore if the enzyme could be dissociated into active monomers, 0.75 M guanidinium chloride was used. Sedimentation velocity measurements demonstrated that this treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
133
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(140 citation statements)
references
References 20 publications
6
133
0
1
Order By: Relevance
“…Intact, catalytically active LPL is a metastable noncovalent dimer, which readily dissociates to inactive monomers. Monomerisation can be induced by moderate concentrations of, for example, guanidinium chloride (Osborne et al, 1985). The heparin affinity of c-LPL indicated that it was dimeric and this was further proved by sedimentation experiments in sucrose density gradients.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Intact, catalytically active LPL is a metastable noncovalent dimer, which readily dissociates to inactive monomers. Monomerisation can be induced by moderate concentrations of, for example, guanidinium chloride (Osborne et al, 1985). The heparin affinity of c-LPL indicated that it was dimeric and this was further proved by sedimentation experiments in sucrose density gradients.…”
Section: Discussionmentioning
confidence: 85%
“…Intact LPL is a non-covalent dimer which can be dissociated by guanidinium chloride to stable, but inactive, monomers (Osborne et al, 1985). To study whether this was the case also for c-LPL, the sedimentation behavior of intact LPL and its monomer was compared to that of c-LPL and to c-LPL treated with guanidinium chloride (Fig.…”
Section: Subunit Interactionmentioning
confidence: 99%
“…The triglyceride/phospholipase ratios of EL-EL and wild-type EL were not statistically different experimentally whatever the cell types used for the transfection. associated almost exclusively with the dimer fraction (24). Sucrose density gradient centrifugation was also used to determine that monomeric LPL refolded in the presence of calcium becomes dimeric (44).…”
Section: Table 1 Triglyceride Lipase and Phospholipase Activities Of mentioning
confidence: 99%
“…The catalytically active forms of both LPL and HL have been shown to be homodimers (18,(21)(22)(23)(24)(25)(26)(27), and in the case of LPL, the orientation of the subunits of the dimer has been shown to be head-to-tail (28 -30). The present study tested the hypothesis that EL also functions as a head-to-tail dimer.…”
mentioning
confidence: 99%
“…Active LPL is known as a noncovalent homodimer. Dissociation of the dimer to the monomeric form renders the lipase inactive (Osborne et al, 1985). These maturation steps are important for the post-translational regulation of enzyme activity (Braun and Severson, 1992;Park et al, 1995;Scow et al, 1998).…”
Section: Introductionmentioning
confidence: 99%